Analisis Pemahaman Konsep dan Sikap Siswa Terhadap Belajar Fisika Pada Materi Hukum Newton Tentang Gerak - Nur Ifani Rizkita; Fatni Mufit (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2022)
Understanding the concept is very important in learning physics. Many studies show that students' understanding of physics concepts is at a low level, including Newton's law of motion in class X SMA. While misconceptions in students are at a high level. Misconceptions can occur because the concepts embedded in students are not the same as expert opinions. The aims of this study were; (1) to determine students' conceptual understanding of Newton's laws of motion, (2) to determine student attitudes towards learning physics and (3) to determine the correlation between students' understanding of physics concepts in Newton's law of motion and students' attitudes towards study physics. The sample or subject in this study were 61 grade X students who had studied Newton's laws of motion. Research data collection was carried out in two ways, namely tests and questionnaires. The instrument for collecting data on understanding Newton's law concepts is the diagnostic four-tier test Newton’s law. The instrument to determine students' attitudes towards learning physics is a questionnaire adopted and then modified from the CLASS (Colorado Learning Attitude about Science Survey). The test data were analyzed statistically and the questionnaire descriptively. The results showed that the students' understanding of Newton's law concepts was very low. The majority of students have misconceptions, especially on Newton's first, second, and third Newton law. Based on the analysis of students' attitudes, it was found that; there are still 29% students who do not like physics lessons and are not interested in increasing the time to study physics. Then, Correlation between student’s understanding of physics concept and attitude towards learning physics, the result showed that the both variable had a correlation value of 0,420. Which means that the both variable has a moderate correlation with a positive direction.